Identifying and costing common gaps in Central and West Africa pharmaceutical regulation - Alfonso, Claudia P.; N’Jambong, Guy B.; Magdy, Alaa; Di Trapani, Laura; Kuwana, Rutendo; Kahsay, Abraham G.; Maïga, Diadié; Ossei-Agyeman-Yeboah, Sybil N. A.; Djitafo Fah, Aimé B.; Ndomondo-Sigonda, Margareth (Frontiers in Medicine, 2024)
Background Regulatory systems strengthening is crucial for catalyzing access to safe and effective medical products and health technologies (MPHT) for all. Identifying and addressing common regulatory gaps through regional approaches could be instrumental for the newly incepted African Medicine Agency. Aims This original study sheds light on common gaps among 10 national regulatory authorities (NRAs) and ways to address them regionally. Objectives The study used NRA self-assessment outcomes to identify common gaps in four critical regulatory pillars and estimate the cost of addressing them from regional perspectives that aimed at raising the maturity level of regulatory institutions. Methods A cross-sectional study, using the WHO Global Benchmarking Tool (GBT), was conducted between 2020 and 2021 with five NRAs from ECCAS and ECOWAS member states that use French and Spanish as lingua franca. Results The 10 NRAs operated in a non-formal-to-reactive approach (ML1-2), which hinders their ability to ensure the quality of MPHT and respond appropriately to public health emergencies. Common gaps were identified in four critical regulatory pillars—good regulatory practices, preparedness for public health emergencies, quality management systems, and substandard and falsified medical products—with overall cost to address gaps estimated at US3.3 million. Contribution We elaborated a reproducible method to strengthen regulatory systems at a regional level to improve equitable access to assured-quality MPHT. Our bottom-up approach could be utilized by RECs to address common gaps through common efforts.